Damping estimation of an offshore wind turbine on a monopile foundation. Issue 4 (1st July 2013) - Devriendt, Christof; Jordaens, Pieter Jan; De Sitter, Gert; Guillaume, Patrick
Abstract : The work presented in this study describes a comparative study between different techniques aimed at identifying the damping values of an offshore wind turbine on a monopile foundation. It will be shown that damping ratios can directly be obtained from vibrations of the tower under ambient excitation from wave and wind loading. The results will be compared with the damping values obtained from a commonly used overspeed stop. Ambient vibration tests have the strong advantage of being more practical and less demanding for the wind turbine in comparison with the overspeed stop. Several identification algorithms, the standard exponential decay method, alternative procedures in the time domain as well as more advanced operational modal analysis techniques in the frequency domain will be applied to the experimental data. These data have been obtained during a short measurement campaign on an offshore wind turbine in the Belgian North Sea. The results of the used methods for estimating the modal damping of a wind turbine excited by ambient excitation will be discussed and compared. This study also presents some aspects related to the practical implementation of the measurements.